Portrait of employees at Alber Brothers Milling Company - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of employees standing in front of the Alber Brothers Milling Company building. Automobiles are visible to the right, with a truck on the end of the row that reads "Peacock Family Flour." On the far left is a building with a sign that reads "freight station Southern Pacific railroad".